Superior performance of ordered macroporous TiNb2O7 anodes for lithium ion batteries: Understanding from the structural and pseudocapacitive insights on achieving high rate capability. (April 2017) - Lou, Shuaifeng; Cheng, Xinqun; Zhao, Yang; Lushington, Andrew; Gao, Jinlong; Li, Qin; Zuo, Pengjian; Wang, Biqiong; Gao, Yunzhi; Ma, Yulin; Du, Chunyu; Yin, Geping; et al.
Abstract: Titanium niobium oxide (TiNb2 O7 ) has been regarded as a promising anode material for high-rate lithium ion batteries (LIBs) due to its potential to operate at high rates with improved safety and high theoretical capacity of 387 mA h g −1 . Herein, three-dimensionally ordered macroporous (3DOM) TiNb2 O7 composed of interconnected single-crystalline nanoparticles was prepared using polystyrene (PS) colloidal crystals as a hard template. The final product yields a homogeneous, continuous, and effective honeycomb-like construction. This architecture provides facile Li + insertion/extraction and fast electron transfer pathway, enabling high-performance lithium ion pseudocapacitive behavior, leading to good electrochemical performance. As a result, the 3DOM-TiNb2 O7 shows a remarkable rate capability (120 mA h g −1 at 50 C) and durable long-term cyclability (82% capacity retention over 1000 cycles at 10 C). The work presented herein holds great promise for future design of material structure, and demonstrates the great potential of TiNb2 O7 as a practical high-rate anode material for LIBs. Graphical abstract: The three-dimensionally ordered macroporous (3DOM) TiNb2 O7 composed of interconnected single-crystalline nanoparticles was prepared using polystyrene colloidal crystals as hard template. This architecture provides facile Li + insertion/extraction and fast electron transfer pathway, and then enables high-effective lithium ion intercalation pseudocapacitive behavior. Highlights: 3DOM-TiNb2 O7 hierarchical nanostructure has been successfully prepared. Our results demonstrate that 3DOM-TiNb2 O7 anode exhibits good high-rate performances and long cycle life due to the unique pseudocapacitive effects. Pseudocapacitive contribution of 3DOM-TiNb2 O7 anode in the total current response was first quantitative calculated.